Corporate Culture in Developing Professionalism of Human Resources in LEMHAMNAS RI - UTAMI, PAULA; ABDULLAH, IRWAN; MARTONO, EDHI (Jurnal Studi Pemerintahan, 2012)
Based on a case study by Lemhannas RI, this work attempts to discuss the relation of professionalismof human resources and corporate culture. The change and growth of corporate culture in anorganization requires strong commitment from those involved in it. Corporate culture should becontinually developed through a persistent socialization, partnership and supervision programs. Theright management of human resources, which follows the basis of management, will give a greatcontribution when applied well. In addition, policy evaluation on corporate culture should includestructural and cultural aspects and be conducted in several steps, including identification of goals andways of completing them, measurement of relevant information activities, analysis of data for aconclusion and recommendation. The recommendation is a crucial step that needs a special attentionfor the restructurization of culture for better results. This study concludes that interaction betweenstructure and culture is a key and pre-condition for the growth of a better and conducive corporateculture for accomplishing the goals of organization.